0068 Introduction of in situ simulation in YMET teaching: A novel approach. (2nd November 2015) - Farooq, Omer; Sallis, Sue; Chambers, Julia; Riby, Stuart; Gay, Christopher; Purva, Makani
Abstract : YMET (Yorkshire Maternal Emergency Training) has traditionally utilised drills training in classroom environment. In situ simulation (simulation in the workplace) improves realism and additionally identifies latent errors 1 (potential hazards in workplace), which can improve patient safety. Our aim was to improve confidence levels in managing an unwell patient and to identify latent errors to improve patient safety. Methods: In situ simulation was performed on the labour ward using postpartum haemorrhage, pre-eclampsia and maternal cardiac arrest scenarios. 30 candidates participated which included midwives, obstetricians and anaesthetists. Participants were given pre- and post-simulation questionnaire to evaluate improvement in confidence levels with regards to managing an emergency patient. Debriefing was performed immediately post scenario. Latent errors highlighted were graded according to NPSA risk matrix 2 and reported to the department with recommendations. Results: Seven latent errors were identified (Medicine 1, Training 6) and reported after grading according to NPSA risk matrix. Our results also demonstrate that 66% of the participants felt considerably confident in managing unwell patients, 86% were able to positively figured out changes in their practice that were required to improve individual and team performance and 80% had knowledge gaps amply highlighted by in situ simulation exercise. More than half of the participants rated feedback as very constructive. More than 80% highly recommended regular simulation sessions. Impact on practice: Introduction of in situ simulation in YMET training has helped in knowledge enhancement and latent errors identification. Recurring gaps in knowledge are highlighted and are dealt with more focused debriefing. Delegates did not realise that perimortem packs were available on resus trolleys. Therefore a visible red sticker is now placed on all trolleys to alert staff to its presence. Although small number of participants has undergone this training, the sessions have been extremely productive. References: Patterson MD, Geis GL, Falcone RA, et al . In situ simulation: detection of safety threats and teamwork training in a high risk emergency department. BMJ Qual Saf 2013;22(6):468–77 National Patient Safety Agency. A risk matrix for risk managers. NHS 2008